2020
DOI: 10.1074/jbc.ra120.013748
|View full text |Cite
|
Sign up to set email alerts
|

The O2-independent pathway of ubiquinone biosynthesis is essential for denitrification in Pseudomonas aeruginosa

Abstract: Many proteobacteria, such as Escherichia coli, contain two main types of quinones: benzoquinones, represented by ubiquinone (UQ) and naphthoquinones, such as menaquinone (MK), and dimethyl-menaquinone (DMK). MK and DMK function predominantly in anaerobic respiratory chains, whereas UQ is the major electron carrier in the reduction of dioxygen. However, this division of labor is probably not very strict. Indeed, a pathway that produces UQ under anaerobic conditions in an UbiU-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 53 publications
(68 reference statements)
6
38
0
Order By: Relevance
“…Other genes of this category include moeB (SGRAN_0222), an unlinked gene involved in Mo cofactor biosynthesis, most of the components of the cyoABCDEregBA operon, (SGRAN_2997-_2991) encoding a bo3 -type quinol oxidase electron transfer chain and the redox responsive regBA two-component regulatory system 18 . yhbTUV operon (SGRAN_3858-_3860) is one of the most induced operons in anaerobiosis 17 and it is involved in the recently described O 2 -independent ubiquinone biosynthesis pathway, proposed to be renamed ubiTUV 35 , and it is essential for denitrification in Pseudomonas 36 . Althought dRNA-Seq showed that expression of the distal genes of this operon was still maintained to some extent in the Δ narG mutant, the , induction kinetics of ubiU in Δ fnr and in Δ narG mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes of this category include moeB (SGRAN_0222), an unlinked gene involved in Mo cofactor biosynthesis, most of the components of the cyoABCDEregBA operon, (SGRAN_2997-_2991) encoding a bo3 -type quinol oxidase electron transfer chain and the redox responsive regBA two-component regulatory system 18 . yhbTUV operon (SGRAN_3858-_3860) is one of the most induced operons in anaerobiosis 17 and it is involved in the recently described O 2 -independent ubiquinone biosynthesis pathway, proposed to be renamed ubiTUV 35 , and it is essential for denitrification in Pseudomonas 36 . Althought dRNA-Seq showed that expression of the distal genes of this operon was still maintained to some extent in the Δ narG mutant, the , induction kinetics of ubiU in Δ fnr and in Δ narG mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa, contain UQ as sole quinone 2 . We found that the ubiT, ubiU and ubiV genes are essential for UQ production by P. aeruginosa in anoxic conditions and that these genes are required for denitrification 56 , a metabolism on which P. aeruginosa heavily relies to develop in the lungs of cystic fibrosis patients.…”
Section: Discovery Of a Conserved O2-independent Pathwaymentioning
confidence: 89%
“…Based on the observation that E. coli was able to synthesize UQ under anoxic conditions, the existence of a UQ biosynthesis pathway independent from O2 had long been hypothesized 55 . This pathway remained uncharacterized until 2019, when we identified three genes, ubiT, ubiU and ubiV which are required for UQ biosynthesis under anoxic conditions but are dispensable under oxic conditions 46 we also hypothesized that UbiU and UbiV may participate in the two other hydroxylation steps of the anaerobic UQ pathway, thus substituting for UbiI and UbiH of the O2-dependent pathway (Figure 3A) 46,56 .…”
Section: Discovery Of a Conserved O2-independent Pathwaymentioning
confidence: 98%
“…For anaerobic UQ9 production, a recent study [37] demonstrated that UQ9 can be produced by an alternate pathway within the UQ9 biosynthesis chain. The biosynthetic proteins are shared between aerobic and anaerobic pathways except for the ones that catalyze the three reactions associated with hydroxylation of intermediate metabolites (Fig.…”
Section: Anaerobic Growthmentioning
confidence: 99%